Biopsy interpretation of the central nervous system - Schniederjan, Matthew J. (Biopsy interpretation series, 2011)
"This new book carries on a strong tradition of diagnostically oriented texts established by the Biopsy Interpretation Series, in the present case focused on lesions of the Central Nervous System. Our purpose is to provide a practical guide and concise reference that can be a companion text for the general surgical pathologist, trainees in pathology and neuropathology, and clinicians who treat patients with neurological diseases that require surgical sampling. Given the heavy orientation of the Biopsy Interpretation Series to the busy and serious-minded diagnostician, we have taken this opportunity to create something new and, we think, useful. While there are certainly several excellent books on neuropathology and surgical neuropathology, the majority are reference texts that are comprehensive and encyclopedic, making them less than optimal on a daily basis to assist with interpretation. Because the central concern here is with establishing the correct diagnosis, the content is aimed at anticipating difficult diagnostic decisions and providing concise and reliable guide to their resolution"--Provided by publisher.